Application of Resource Efficient and Cleaner Production Approach in the Accommodation Sector of the Balkan Region - Assenova, Mariana; Georgiev, Zdravko; Dunjic, Branko (European Journal of Sustainable Development, 2016)
The aim of the paper is to present the results of the application of the RECP methodological approach in the accommodation sector of countries from the Balkan region – Croatia, Serbia, Montenegro and Albania. It is based on the experience from 2015 in 20 hotels (5 in each country), undergone detailed in-plant assessments. The methodology lays down on the understanding that RECP is a continuous application of an integrated preventive environmental strategy applied to processes, products and services to increase overall efficiency, and reduce risks to humans and the environment. Based on the obtained data for the material and energy flows, the paper provides a summary and analyses of the most often proposed and implemented measures. A set of absolute and relative indicators (KPIs) for resources use (energy and water consumption) and pollution generated (air emission and waste water) is used and the expected change due to the implementation of the accepted options is calculated. The performance of the accommodation facilities is compared to the international benchmarks available. The results of the study come to show the great potential of the accommodation sector for more sustainable production and outline the focal points of intervention needed. Keywords: resource efficiency, cleaner production, monitoring, performance indicators, benchmarks, accommodation sector